Election Night at Bruce Bronzan State Assembly Campaign Headquarters in Roos-Atkins Building - Watkins, Howard::::::::: (1978)
Bob Quesada, John Donaldson (pink shirt), Nick Bronzan, Polly Victor, Linda Bronzan, Dave Brodie, Beth Meyerson, ?, Bill Carlson, Bruce Bronzan, ?